Effective classroom management : the essentials - Becker, Jimmy (New York, NY : Larsen & Keller, 2025)
"A practical guide providing teachers with essential strategies for managing the classroom effectively. Topics include classroom structure, student behavior, expectations, routines, and positive teacher-student relationships."
Includes bibliographical references and index.
Keywords: Classroom management; Teaching -- Methods; Learning environment